RETRACTED: Case Studies in Management Science Research for Digitalization and Sustainability Development - Dzwigol Henryk (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 456, 00002 (2023), https://doi.org/10.1051/e3sconf/202345600002